Regional Roadmap – Accelerating Terrestrial 5G Deployment - Roberto Ercole (International Telecommunications Society (ITS), 2019)
The overarching question this paper is trying to address is: "Can we rely on market forces and competition to deliver 5G the way it delivered GSM, 3G, and 4G, or do we need another approach?". The metric used in the paper is payback period, which while it is not an economically "rigorous" method, it does resonate with some industry decision makers. It could be considered the first hurdle any investment proposal needs to clear before progressing to say a detailed NPV analysis. The impact of various assumptions is explored in the costs and payback figures. The paper is not an economic analysis but an industry participant's view and examines what might influence industry players who will take the risks with large capital investments running into 100's million in many markets. The author believes that only the current mobile opcos in the region are likely to make the investments to deliver wide area 5G (as opposed to very isolated hot-spot coverage). Therefore, it is important to understand how mobile opcos and their investors might perceive 5G. The lack of faith in the 5G business model from some in the industry is not a good sign. The paper also looks at what regulators might do (if they wish to encourage 5G) to speed up deployment of 5G. Regulatory measures might be consideration on spectrum licence fees or other taxation on mobile, as well as considering the number of operators who cover rural areas. Other issues that can help will be the reduction of regulatory uncertainty due to international radio crossborder interference - which may be an issue in the region for new 5G bands. This paper follows on from the paper written by the author and delivered at the SAMENA Leaders' Summit in May 18, but is the view of the author alone, and not of SAMENA.
Keywords: 330